Labor Market Signaling and Self-Confidence: Wage Compression and the Gender Pay Gap - Santos-Pinto, Luís (Journal of Labor Economics, 2012)
I extend Spence’s signaling model by assuming that some workers are overconfident—they underestimate their marginal cost of acquiring education—and some are underconfident. Firms cannot observe workers’ productive abilities and beliefs but know the fractions of high-ability, overconfident, and underconfident workers. I find that biased beliefs lower the wage spread and compress the wages of unbiased workers. I show that gender differences in self-confidence can contribute to the gender pay gap. If education raises productivity, men are overconfident, and women underconfident, then women will, on average, earn less than men. Finally, I show that biased beliefs can improve welfare.